Segmental dilatation of colon detected on prenatal ultrasound - Naoko Uga; Tatsuya Suzuki; Kouhei Sakurai; Tetsuya Tsukamoto; Tomonori Tsuchiya; Yasuhiro Kondo; Atsuki Naoe; Shunsuke Watanabe; Toshihiro Yasui; Fujio Hara (Journal of Pediatric Surgery Case Reports, 2019)
Segmental dilatation of the colon is a rare condition in which there is an abrupt segment of dilated colon between regions of normal colon, without obstruction. The condition causes bilious vomiting and abdominal distention in the neonate, and causes constipation or anemia in infants and adults. We herein report a case of segmental dilatation of the descending colon detected on prenatal sonography. The patient was born at 39 weeks' gestation, weighing 3720 g. At 10 months, he developed constipation and enterocolitis. At 1 year of age, the patient underwent laparoscopic-assisted resection of dilated colon with end-to-end anastomosis. Resection of the dilated segment alone was not sufficient, according to frozen biopsy. Therefore, we resected an additional 3 cm both proximally and distally, where teniae coli were grossly evident. Histological examination of the dilated segment showed muscular layer hypertrophy with hyperplasia and widening of Auerbach's plexus. The patient's 7-month follow-up was unremarkable. With improved quality of prenatal sonography, more patients will be diagnosed with segmental dilatation of the intestine. This is the first report in the English literature of segmental dilatation of the colon detected on prenatal ultrasound. Keywords: Segmental dilatation of colon, Segmental dilatation of intestine, Prenatal ultrasound